The Political (In)Stability of Funded Social Security - Roel M. W. J. Beetsma; Oliwia Komada; Krzysztof Makarski; Joanna Tyrowicz (Institute of Labor Economics (IZA), 2021)
We analyze the political stability of funded social security. Using a stylized theoretical framework we study the mechanisms behind governments capturing social security assets in order to lower current taxes. The results and the driving mechanisms carry over to a fully-fledged and carefully calibrated overlapping generations model with an aging population. Funding is efficient in a Kaldor-Hicks sense. We demonstrate that, even though we can rationalize the actual introduction of a two-pillar defined-contribution scheme with funding through a majority vote, a new vote to curtail the funded pillar through asset capture or permanent diversion of contributions to the pay-as-you-go pillar always receives majority support. For those alive and thus allowed to vote, the temporary reduction in taxes outweighs the reduction in retirement benefits. This result is robust to substantial intra-cohort heterogeneity and other extensions, and only overturned with a sufficient degree of altruism. Our analysis rationalizes the experience of Central and Eastern European countries, who rolled back their funded pension pillars soon after setting them up.
Keywords: H55; D72; E17; E27; 330; social security; funding; pay-as-you-go; asset capture; majority vote; welfare